Technetium-99m-labeled genistein as a potential radical scavenging agent - Danni Ramdhani; Maula Eka Sriyani; Flamboyan Ayu (Wolters Kluwer Medknow Publications, 2019)
The purpose of this study was to determine the optimum conditions for labeling genistein compounds with technetium-99m (99mTc) radionuclides and the percentage of purity obtained in accordance with the requirements of the United State Pharmacopeia. The method used is optimization of several parameters including pH, SnCl2.2H2O as reducing agents, genistein concentration, and incubation time. The results showed that the optimum conditions for labeling 99mTc-Genistein were obtained under conditions of pH 8, the amount of SnCl2.2H2O reducing agents was 30 μg, 0.5 mg genistein, and in 10 min. The optimization of this condition resulted in radiochemical purity in the labeling of 99mTc-Genistein compounds at 95.43% ± 0.85%. The radiochemical purity of the labeling of 99mTc-Genistein compounds has met the requirements of the United State Pharmacopeia as a compound marked for diagnosis of more than 90%.